Relationship between Gestational Age and Neonatorum Asphyxia in the Neonatal Intensive Care Unit - Dwy Riska Andansari; Sunanto; Iis Hanifah (Health and Technology Journal (HTechJ), 2023)
Asphyxia neonatorum is a condition where the baby does not breathe spontaneously and regularly immediately after birth; this condition can be accompanied by hypoxia, hypercapnia, and up to acidosis. This study aims to analyze the relationship between gestational age and the incidence of neonatal asphyxia in the Neonatal Intensive Care Unit at Tongas Hospital, Probolinggo District. This research is quantitative with a correlational design using a cross-sectional study approach with a total of 35 respondents using an accidental sampling technique. Data collection includes coding, editing, and tabulating, then analyzed manually and by computer with the Spearman Rank Test. Based on data from 35 respondents who were studied in the period June 20, 2022, to August 31, 2022, the majority were preterm, with a total of 17 respondents (48.6%), including mild asphyxia 4 (11.4%) and moderate asphyxia 13 respondents (37.1%) %). With p=0.000 (a=0.05), there is a relationship between gestational age and the incidence of neonatal asphyxia in the Neonatal Intensive Care Unit at Tongas Hospital, Probolinggo Regency. Midwives are expected to immediately determine gestational age because it is important to predict delivery to prevent neonatal asphyxia.